Antonia ROTHMAYR. The Structure of Stative Verbs. Amsterdam / Philadelphia: John Benjamins Publishing Company, 2009. 216 pp. ISBN 978 90 272 5526 6 - Cunha, Luís Filipe (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2017)
.